Human Relations Approach of Organizational Communication in Kelurahan LPDP UGM Bahagia 2023 - Hidayatullah, Haqqi; Tiandini, Novian (Universitas Gadjah Mada, 2026)
Communication is crucial in organizational management. Many issues within organizations stem from communication problems, yet effective communication can often resolve them. Kelurahan LPDP UGM Bahagia, the largest organization of LPDP scholarship awardees globally with 3,866 recipients in 2023, requires a strategic approach to organizational communication. One such approach is the human relations approach, which emphasizes informal relationships between superiors and subordinates and prioritizes moral and psychological aspects over legal aspects within the organization. This research aims to explore how the human relations approach is implemented in organizational communication at Kelurahan LPDP UGM Bahagia in 2023. A descriptive method with a qualitative approach was employed to gain a deeper understanding of observed situations without hypothesis testing or predictions. Findings indicate that Kelurahan LPDP UGM Bahagia 2023 employs the human relations approach to enhance organizational effectiveness through improved communication, collaboration, and social cohesion. By integrating diverse communication contents, directions, channels, and styles, the organization strives to foster a supportive and adaptive environment conducive to achieving its vision and mission.